Peanut crop yield under full and deficit irrigation in the reproductive phase - Antonio M. P. Bertino; Rogério T. de Faria; Anderson P. Coelho; Ancelmo Cazuza Neto (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Peanut cultivation has national and global significance in agriculture and industry. Under water-limited conditions, its yield decreases to the extent that it compromises the success of the exploitation. This study focused on evaluating peanut crop yield and production components under full and deficit irrigation applied in the reproductive phase, to determine the impact of water supply on the yield of peanuts grown in the off-season in the State of São Paulo, Brazil. The experiment was conducted for two years and followed a randomized blocks design with five irrigation levels distributed in strips, with four repetitions. The treatments consisted of crop evapotranspiration replenishments from 100 to 10%. In the first year, under suitable temperatures, the maximum yield reached 3,922 kg ha-1 with the application of 277 mm of irrigation depth and decreased up to 35% with the lowest irrigation depth (48 mm). In the second year, suboptimal temperatures caused a delay in the growing cycle and caused a 33% reduction in crop yields. Despite the potential benefits of deficit irrigation in increasing water productivity, low temperatures pose a risk to peanut yield, especially during the off-season crop in the region.